PARTISIPASI MASYARAKAT DALAM PROSES KEBIJAKAN DAERAH - Manshur, Abdullah (Jurnal Desentralisasi, 2012)
Public policy is a decision to deal with a particular problem situation, that identifies the objectives, principles, ways and means to achieve them. Ability and understanding of policy makers to the policy-making process is very important forthe realization of public policy of rapid, accurate and adequate. The product to suit  the needs of the public policy, the public participation in the policy process is needed in the policy cycle, from policy formulation to policy evaluation. This paper attempts to review the importance of community participation and other forms of public participation in the policy process, in particular policy areas